Outcome of Chemical Versus Surgical Sphincterotomy in Patients with Chronic Anal Fissure - FAROGH ZAHRA, BAKHAT YAWAR, IMTIAZ HUSSAIN, AAMER ZAMAN KHAN, (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To compare the outcome of chemical versus surgical sphincterotomy in patients with chronic anal fissure. Study Design: Observational Comparative Study. Setting: Department of Surgery, Sir Ganga Ram Hospital, Lahore. Subject and Methods: 74 patients who presented with chronic anal fissure at the surgical outdoor of Sir Ganga Ram Hospital, Lahore and who met the inclusion criteria were enrolled in the study after written informed consent. Patients were randomly divided into two groups. Group-A (n=37) was subjected to chemical sphincterotomy while Group-B (n=37) underwent lateral internal sphincterotomy. Patient’s demographic data along with treatment outcome was noted. Results: The age of the patients ranged from 20 to 60 years with a mean age of 39.76±11.74 years in Group-A (chemical sphincterotomy) and 40.65±11.30 years in Group-B (surgical sphincterotomy). Only 29 (39.2%) patient were male while majority 45 (60.8%) patients were female. However there was no significant difference statistically between the two groups in terms of age (p=0.74) and gender (p=0.81). Wound healing was much better in Group-B (surgical sphincterotomy) (97.3%) as compared to Group-A (chemical sphincterotomy) (32.4%) and this difference was statistically significant (p=0.000). Conclusion: Surgical treatment in the form of lateral internal sphincterotomy is extremely effective as compared to chemical sphincterotomy in the form of 0.2% GTN in patients with chronic anal fissure.